CORRELAÇÃO ENTRE TRANSPORTE E HEMATOMAS EM CARCAÇAS DE BOVINOS TRANSPORTADOS POR VIA TERRESTRE - BACHES, Bruna; OLIVEIRA, Dalton Mendes; NUNES, Cris Luana de Castro; PIAZZON, Cleiton José; ESCOBAR, Loraine Saldanha (ANAIS DO ENIC, 2017)
-